Nutritional Status and Symptoms in Preschool Children With Autism Spectrum Disorder: A Two-Center Comparative Study in Chongqing and Hainan Province, China - Zhu, Jiang; Guo, Min; Yang, Ting; Lai, Xi; Tang, Ting; Chen, Jie; Li, Ling; Li, Tingyu (Frontiers in Pediatrics, 2020)
Objective: The study aimed to compare the nutritional status and symptoms of preschool children with autism spectrum disorder (ASD) from two regions of China, and to analyze the association between nutritional status and symptoms of ASD. Methods: In this cross-sectional study, 738 ASD children and 302 typically developing children (TD) were recruited from Chongqing and Hainan of China. Symptoms of ASD children were evaluated with the Autism Behavior Checklist (ABC), Social Responsiveness Scale (SRS), and Childhood Autism Rating Scale (CARS). Neurodevelopment of ASD children was assessed with the Gesell Developmental Scale (GDS). Nutritional status was evaluated by anthropometric measures, biochemical detection of micronutrients, and providing questionnaire and food frequency questionnaire (FFQ) to caregivers. Results: Comparing ASD children with local TD children, ASD children consumed fewer whole grains, milk and dairy products, beans and soy products, vegetables, and fruits than local TD children in both regions. The serum concentrations of folate, vitamin B12 (VB12), and vitamin D (VD) were consistently lower in ASD children in both regions. Comparing the ASD children between the two regions, the ASD children in Chongqing had significantly higher mean scores of CARS, SRS, and ABC than those in Hainan. The ASD children in Chongqing consumed fewer whole grains, seafood, and fruits than those in Hainan. The serum concentrations of ferritin, vitamin A (VA), VB12, and VD were reduced in the ASD children of Chongqing than those in Hainan, and the ASD children in Chongqing had higher deficiency rates of zinc, ferritin, VA, and VD than those in Hainan. The serum levels of VA, VD, and folate showed a negative association with symptom scores of ASD children. VD and zinc levels had a positive association with the GDS scores of ASD children. Conclusions: ASD children exhibit a higher risk of nutrient deficiencies than neurotypical children, and there are regional differences in the nutritional status of ASD children. Micronutrients VA, VD, folate, and zinc levels were correlated with symptoms and development of ASD children. Therefore, it is essential to provide detailed nutrition evaluation and individualized nutrition interventions for ASD children from different backgrounds.